Public Information Services for The Harapan Family Program, Simoro Village, Gumbasa District, Sigi Regency - Ade Irma (Fakultas Ilmu Sosial dan Ilmu Pendidikan Universitas Tadulako, 2022)
According to Article 28F of the 1945 Constitution, the Law on Public Information Disclosure went into effect on May 1, 2010. It was born with the basis and purpose that information is a basic need of everyone for personal development and social environment, as well as an important part of national security. Research This is a descriptive study using a qualitative technique, as well as a research paradigm to describe occurrences. Simoro Village, Gumbasa District, Sigi Regency is the research site. The family of hope program addresses the problem by focusing on public information services. Using Zeithaml's theory (Pasolong, 2008) The five service quality parameters 1) Tangibles; manifested in ineffective and inefficient physical facilities, equipment, staff, and communication materials. 2) Realism, i.e. less accurate or untrustworthy service information. 3) Responsiveness, or the inability to respond to information. 4) Assurance; knowledge remains ineffective and inefficient. 5) Compassion. Officers in the process of providing public information services are still missing.